PENGUATAN LITERASI BUDAYA RIMPU: MEMPERKUAT EKSISTENSI PEREMPUAN ISLAM DI TANAH BIMA - Titin Kurniati Wati; Muh Fahruddin; Deflis Babuta; Hasaruddin Hasaruddin (Unversitas Muhammadiyah Mataram, 2024)
Rimpu culture as a symbol of the existence of Islamic women in the land of Bima. Rimpu is a sarong used to cover the private parts and has been an important part of the culture of the Bima people since the beginning of the spread of Islam in the region. This research uses library methods to gain a deeper understanding of Rimpu culture. The research results show that Rimpu is made from sarong material and has existed in Bima since the beginning of the arrival of Islam, where Rimpu was applied to the Bima sultanate. Rimpu has several types, including ordinary Rimpu and Rimpu Mpida. Rimpu is usually divided into Rimpu Colo and Rimpu Cili, while Rimpu Mpida consists of Rimpu Mpida, Rimpu Gala, and Rimpu Cili.Rimpu has a dual function in responding to current developments. First, as a religious identity, where the use of Rimpu is one way for Bima women to show their religious beliefs. Second, Rimpu is also a characteristic of Bima culture which is embedded in the daily life of its people. And third, Rimpu acts as a protector for women in interacting with the opposite sex, protecting their honor and chastity. Currently, the Bima government is trying to preserve Rimpu culture by holding a cultural parade every year. This effort aims to promote and introduce Rimpu culture to the wider community and encourage understanding and appreciation of cultural heritage.